HOTEL RESORT DANAU LAIT - Arif Affandi; Jawas Dwijo Putro; Emilya Kalsum (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Danau Lait became famous after going viral on social media because of its natural beauty and uniqueness. Located in Subah Village, Sanggau Regency in West Kalimantan Province. Currently, Danau Lait is starting to be visited by many people. Based on references to the number of visitors to Lake Lait in recent months, it has reached more than 8000 visitors. The surge in visitors to Lake Lait is not matched by the accommodation that accommodates the needs of visitors. Therefore, we need a place or place for refreshing and comfortable rest for visitors, namely in the form of a Resort hotel. The function of a Resort hotel is not only to stay but also to enjoy the natural attractions of Danau Lait. The design of this Resort hotel uses the concept of a Neo-vernacular approach, which is a combination of the concept of traditional buildings and modern buildings which are emphasized on the building's facade. The use of this concept also aims to give an identity to the Hotel Resort Danau Lait building. Based on the existing problems, it is possible to create a Resort hotel with a Neo-vernacular approach that can accommodate the needs of tourists visiting Danau Lait.